1976
DOI: 10.1288/00005537-197608000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The use of steroids in bell's palsy: A prospective controlled study

Abstract: A prospective, controlled, double-blind study was designed to evaluate the effect of steroid treatment on the natural history of Bell's palsy. Fifty-one patients were included in the study between 1972 and 1974. The patients were evaluated and started on treatment within two days of onset of Bell's palsy and followed for six months. Treatment was given in randomized double-blind fashion and consisted of either vitamins or a total of 410 mg of prednisone plus vitamins in descending doses over 10 days. The recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…Table 1 summarizes these studies and includes 2 of the studies reviewed in the original guideline that attained a grading of Class II or better. 16,17 Only Class I and Class II studies are discussed further. The 2 Class I studies 8,11 randomized patients to steroids vs placebo and described concealed allocation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes these studies and includes 2 of the studies reviewed in the original guideline that attained a grading of Class II or better. 16,17 Only Class I and Class II studies are discussed further. The 2 Class I studies 8,11 randomized patients to steroids vs placebo and described concealed allocation.…”
mentioning
confidence: 99%
“…The 3 Class II studies [15][16][17] did not describe concealed allocation. These studies enrolled fewer than 100 patients each and described complete follow-up and masked outcome assessment.…”
mentioning
confidence: 99%
“…7 " Your colleague, however, might find this quote to contradict the first expert: "Bell's palsy remains without a proven efficacious treatment. 8 " It is often possible to find credible experts with conflicting opinions.…”
Section: The Evidence-practice Gapmentioning
confidence: 99%
“…In it she has an article from May et al, 8 published in 1975, in which the authors randomly assigned patients with Bell's palsy to receive steroids or placebo. 8 There was no significant difference in facial functional outcomes between the two groups. The authors concluded steroids were ineffective.…”
Section: The Evidence-practice Gapmentioning
confidence: 99%
“…In IFNP, it has been proven that using steroids is more effective than placebo [2] . Although steroid therapy, which will be given at an early stage in IFNP, slows the spontaneous progress in paralysis and accelerates recovery [3] , some studies reported that steroids do not provide beneficial effects [4] . Steroids are also used in the treatment of PFNP.…”
Section: Introductionmentioning
confidence: 99%